An Examination of Magnetosphere‐Ionosphere Influences During a SAPS Event. Issue 19 (6th October 2021) - Kunduri, B. S. R.; Baker, J. B. H.; Ruohoniemi, J. M.; Coster, A. J.; Vines, S. K.; Anderson, B. J.; Shepherd, S. G.; Chartier, A. T.
Abstract: The sub‐auroral polarization stream (SAPS) is a region of westward high velocity plasma convection equatorward of the auroral oval that plays an important role in mid‐latitude space weather dynamics. In this study, we present observations of SAPS flows extending across the North American sector observed during the recovery phase of a minor geomagnetic storm. A resurgence in substorm activity drove a new set of field‐aligned currents (FACs) into the ionosphere, initiating the SAPS. An upward FAC system is the most prominent feature spreading across most SAPS local times, except near dusk, where a downward current system is pronounced. The location of SAPS flows remained relatively constant, firmly inside the trough, independent of the variability in the location and intensity of the FACs. The SAPS flows were sustained even after the FACs weakened and retreated polewards with a decline in geomagnetic activity. The observations indicate that the mid‐latitude trough plays a crucial role in determining the location of the SAPS and that SAPS flows can be sustained even after the magnetospheric driver has weakened. Plain Language Summary: The sub‐auroral polarization stream (SAPS) is an important phenomenon that controls the dynamics of the sub‐auroral region. While SAPS has been studied for several decades, our understanding of the drivers of this phenomenon is still limited. In this study, we analyze an event to examine the validity of different SAPS mechanisms, and to determine the importance of the ionosphere‐thermosphere system in driving and sustaining SAPS flows. We find that the ionosphere can play an important role in determining SAPS location and that SAPS can be sustained even after the magnetospheric driver has weakened. Key Points: During the recovery phase of a small geomagnetic storm, substorm activity drove a new set of FACs into the ionosphere, initiating a sub‐auroral polarization stream (SAPS) The SAPS location remained relatively constant, firmly inside the trough, independent of the variability in the field‐aligned currents (FACs) The SAPS flows were sustained for almost an hour after the FACs weakened and retreated polewards